PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP LOYALITAS KARYAWAN DI HOTEL “BINTANG LIMA” PEKANBARU - Suryani Situmorang; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the effect of organizational climate and organizational commitment to employee loyalty partial and simultaneous. This study used a questionnaire as a data collection tool that is distributed to 26 respondents to the employees of the hotel